Pengaruh Latihan Progressive Muscle Relaxation Terhadap Status Fungsional Dalam Konteks Asuhan Keperawatan Pasien Kanker dengan Kemoterapi di RS Dr.Wahidin Sudirohusodo Makassar - Haryati Haryati; Ratna Sitorus (Halu Oleo University, 2015)
Chemotherapy is one of the cancer treatment that could provide many side effects and decrease the functional status and quality of life cancer patients. Progressive muscle relaxation (PMR) training is one of the nursing intervention that leads to decreased physical and phsycological effect from chemotherapy. The purpose of this study was to identify the effect of progressive muscle relaxation training on functional status in the context of the nursing care for cancer patients with chemotherapy. This study was a quasi experimental using a nonequivalent control group with pretest and posttest design. The sample was cancer patients who received chemotherapy and inpatient in RS Dr. Wahidin Sudirohusodo Makassar. A concecutive sampling was used as the sample collection method and 48 subjects were obtained this study, divided into two groups, each group consisted of twenty four subjects as intervention group who were given PMR training twice a day for seven days, and twenty four subjects as control group who were not given PMR training. The instrument that used in this study were demography form and Functional Living Index-Cancer to measure functional status which consisted 22 questions with 7-point Likert-Type linear analog scale. A T test was used to examine the differences of the mean of functional status scores and each dimension. The finding showed that there was a significant increased of the mean of functional status after PMR training in intervention group (p=0,000). It means that PMR training has an effect in increasing level of functional status in cancer patients with chemotherapy. It is recommended to apply PMR training as a nursing intervention to cancer patients with chemotherapy and suggested to conduct futher research using more samples.Key Word: cancer, chemotherapy, functional status, progressive muscle relaxation